PEMBELAJARAN PEMECAHAN MASALAH PENJUMLAHAN DENGAN TEKNIK MENYIMPAN PADA SISWA KELAS 2 DENGAN MENGGUNAKAN METODE PROBLEM SOLVING - Ai Supriati; Sylvia Rabbani (COLLASE (Creative of Learning Students Elementary Education), 2021)
Problem solving is one of the abilities that must be mastered by students after learning mathematics, solving mathematical problem solving is one of the problems that are discussed in this study, the purpose of this study is to find out how to apply the addition problem solving abilities with storing techniques, the method used in this research is descriptive qualitative, the subject of this research is the second grade students of one of the public elementary schools in the city of Cikalong wetan. From the results of this study, it can be explained that second grade students like learning to use the Problem solving method, in addition students and teachers give a positive response to the learning problem solving addition by storing techniques using the problem solving method, but still found students who have difficulty in identifying known data, asked and implemented strategies to solve problems. From the discussion it can be concluded that the ability to solve the problem of addition by storing techniques in second grade students is still relatively low and needs to be given exercises so that students are accustomed to solving difficult questions in the form of story questions.